Workflows and individual differences during visually guided routine tasks in a road traffic management control room. (May 2017) - Starke, Sandra D.; Baber, Chris; Cooke, Neil J.; Howes, Andrew
Abstract: Road traffic control rooms rely on human operators to monitor and interact with information presented on multiple displays. Past studies have found inconsistent use of available visual information sources in such settings across different domains. In this study, we aimed to broaden the understanding of observer behaviour in control rooms by analysing a case study in road traffic control. We conducted a field study in a live road traffic control room where five operators responded to incidents while wearing a mobile eye tracker. Using qualitative and quantitative approaches, we investigated the operators' workflow using ergonomics methods and quantified visual information sampling. We found that individuals showed differing preferences for viewing modalities and weighting of task components, with a strong coupling between eye and head movement. For the quantitative analysis of the eye tracking data, we propose a number of metrics which may prove useful to compare visual sampling behaviour across domains in future. Highlights: Qualitative and quantitative analysis of information acquisition and workflow in a live road traffic control room. Individual differences for preferred viewing modality, scan patterns and time spent on chosen regions of interest. Despite heterogeneous sampling approaches, subgoal completion remained structured through an incident log.